2021
DOI: 10.3389/fpsyg.2021.648443
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' Perception of Student Coping With Emergency Remote Instruction During the COVID-19 Pandemic: The Relative Impact of Educator Demographics and Professional Adaptation and Adjustment

Abstract: The outbreak of the COVID-19 pandemic has upended lives and thrown the taken for granted into disarray. One of the most affected groups were teachers and students, faced with the necessity of school closures and—where logistically feasible—an urgent shift to emergency remote instruction, often with little prior notice. In this contribution, based on an online survey involving participants from 91 countries, we offer a perspective bridging the two groups, by investigating the role of teachers' demographics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 84 publications
(106 reference statements)
2
27
0
7
Order By: Relevance
“…Bensaid and Brahimi (2021) likewise attributed the successful maintenance of the learning cycle in higher education institutions in the Gulf to their already established distance education, swift administration and policy steps, and access to resources. Jelińska and Paradowski (2021b) in turn revealed how teachers' perception of how their students were coping with the novel situation was influenced by their own demographics and professional adaptation to emergency remote teaching.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bensaid and Brahimi (2021) likewise attributed the successful maintenance of the learning cycle in higher education institutions in the Gulf to their already established distance education, swift administration and policy steps, and access to resources. Jelińska and Paradowski (2021b) in turn revealed how teachers' perception of how their students were coping with the novel situation was influenced by their own demographics and professional adaptation to emergency remote teaching.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, faculty perceptions of student expectations of faculty during the pandemic response were examined. Teacher perceptions of students' strengths and weaknesses impact faculty expectations and instructional methods (Jelińska & Paradowski, 2021;Reimers & Schleicher, 2020). Awareness of faculty perceptions of how students are handling ERT can guide training and adjustments in the role faculty play in guiding student learning through a crisis.…”
Section: Faculty Perceptions Of Student Learningmentioning
confidence: 99%
“…Although we do not have enough data to make a strong inference about the quality and depth of students' learning, the teachers' statements indicate that many students had a hard time with the self-learning of new mathematical content. In a study of teachers' perceptions of students dealing with emergency remote education, Jelińska and Paradowski (2021) reported that older students (higher secondary and tertiary levels) could better adapt and take control of their learning because they have better-developed self-learning strategies, unlike younger students.…”
Section: Organisation Of Classroom Practice Assessment and Utilisation Of Resourcesmentioning
confidence: 99%
“…All the above emphasises a teacher's role as a facilitator who proactively supports students and their learning during remote education. Studies examining teachers' workloads during the pandemic have shown that remote education has increased a teacher's sense of responsibility for student achievement and their job-related stress levels (e.g., Collie, 2021;Jelińska & Paradowski, 2021). Some students did not perceive this mode of education as compulsory, carrying with it certain obligations and responsibilities, because in the first and last month, many were not active in the virtual classrooms.…”
Section: Influence Of Social and Institutional Parametersmentioning
confidence: 99%